Estudo das feições lineares observadas em dados aeromagnéticos da Bacia do Solimões a partir de imagens digitais de sombreamento do relevo anômalo total - AFFONSO, Alexandre de Oliveira (Universidade Federal do Pará, 2014)
The Solimões Basin is a magnetically complex basin characterized by a superposition of different linear magnetic anomalies. These anomalies reflect the different tectonic episodes that have occured in the Amazon Region during the Precambriam and Phanerozoic. In this work, a shaded relief method of digital image processing was applied to the aeromagnetic data from the Solimões Basin. The characteristics of this method, which allow its use as a strike enhancement filter, clarified important aspects of the relationships between magnetic lineations oriented E—W, NE—SW, e NW—SE. A magnetic lineation pattern was identified which reflects the presence of dextral strike-slip fault zones that have a preferential orientation in the E—W direction. The interaction between these systems promoted the development of a convergent stress regime which caused the formation of reversel faults associated with E—W and NE—SW magnetic lineaments; together with directional duplexes, forming positive and negative flower structures associated with N70-80E and N70-80W magnetic lineaments. A parallel quantitative analysis was also performed on the aeromagnetic data which attempts to quantify two importants aspects of these linear magnetic anomalies shown on the digital images. The first analysis was based on a forward modeling of the aeromagnetic data using a superposition of two-dimensional prismatic bodies. It is shown that these magnetic linear features can be explained by the superposition of highly magnetized basement sources and higher frequency shallow sources associated with reverse faulting of diabase sill's present in the Paleozoic sediments of the Basin. The second analysis, which was based on cross-covariance methods, calculated the offsets present in the NE—SW magnetic lineaments along dextral E—W directions. This analysis supports the explanation that the magnetic pattern from this region can be explained by means of lateral offsets presumably along pre-existing zones of weakness (Precambrian, Paleozoic), during the Mesozoic and Cenozoic.